2013
DOI: 10.1038/cddis.2013.380
|View full text |Cite
|
Sign up to set email alerts
|

IBP-mediated suppression of autophagy promotes growth and metastasis of breast cancer cells via activating mTORC2/Akt/FOXO3a signaling pathway

Abstract: Interferon regulatory factor-4 binding protein (IBP) is a novel upstream activator of Rho GTPases. Our previous studies have shown that ectopic expression of IBP was correlated with malignant behaviors of human breast cancer cells, and invasive human breast cancer had high expression of IBP that promoted the proliferation of these cells. However, it remains unknown whether autophagy inhibition contributes to IBP-mediated tumorigenesis. In this study, we for the first time, reported that upregulation of IBP exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 56 publications
(72 reference statements)
4
34
1
Order By: Relevance
“…This suggests that even though doxorubicin activates mTORC1, doxorubicin-elicited inhibition of autophagy is not dependent on up-regulation of mTORC1 activity. It is also worth noting that mTORC2 is an inhibitor of autophagy (both macroautophagy 32 and chaperone-mediated autophagy 33 ). Therefore, it is likely that doxorubicin’s inhibition of autophagy in cardiomyocytes is not dependent on mTORC2 activity either.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that even though doxorubicin activates mTORC1, doxorubicin-elicited inhibition of autophagy is not dependent on up-regulation of mTORC1 activity. It is also worth noting that mTORC2 is an inhibitor of autophagy (both macroautophagy 32 and chaperone-mediated autophagy 33 ). Therefore, it is likely that doxorubicin’s inhibition of autophagy in cardiomyocytes is not dependent on mTORC2 activity either.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al (13) revealed that IBP was highly expressed in breast cancer, but expressed at low levels in normal breast tissues, and that the ectopic expression of IBP was correlated with the malignant behavior of human breast cancer cells. Furthermore, Chen et al (32) suggested that IBP-mediated suppression of autophagy promotes the growth and metastasis of breast cancer cells by activating the mechanistic target of rapamycin kinase complex 2/protein kinase B/forkhead box O3a signaling pathway. Yang et al (33) demonstrated that IBP was a target gene of tumor protein 53 and that it suppresses cisplatin-induced apoptosis of breast cancer cells.…”
Section: Os Monthsmentioning
confidence: 99%
“…mTORC2 was reported to regulate the actin cytoskeleton rearrangement [60]. Meanwhile, evidences certified that mTORC2 was a critical component in the regulation of cell proliferation and metastasis by the effect of autophagy [61].…”
Section: Discussionmentioning
confidence: 99%